The right to science: then and now - Porsdam, Helle; Mann, Sebastian Porsdam (Cambridge University Press, 2022)
That everyone has a human right to enjoy the benefits of the progress of science and its applications comes as a surprise to many. Nevertheless, this right is pertinent to numerous issues at the intersection of science and society: open access; 'dual use' science; access to ownership and dissemination of data, knowledge, methods and the affordances and applications thereof; as well as the role of international co-operation, human dignity and other human rights in relation to science and its products. As we advance towards superintelligence, quantum computing, drone swarms, and life-extension technology, serious policy decisions will be made at the national and international levels. The human right to science provides an ideal tool to do so, backed up as it is by international law, political heft, and normative weight. This book is the first sustained attempt at turning this wonder of foresight into an actionable and justiciable right.